(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
The study aimed to reveal the scientific, social, economic, and aesthetic values ​​that are promoted and reinforced by the animation programs directed to the child, by analyzing a sample of the programs directed to such stage of childhood. The study adopted the descriptive analytical approach for the programs of the "Baraem" channel, and its population consisted of an intentional sample of "118" episodes in four selected programs, using the sample’s content analysis form, divided into the content category and the form category. The study concluded with results, the most important of which was that the study sample contained the values ​​of the animation programs directed to the schoolchild in the following order: Social values came in the first place with a number of 2850 values and a percentage of 39.3%. Scientific values came in the second place with a number of 1900 values and a percentage of 26.2%. Aesthetic values came in the third place with a number of 1690 values and a percentage of 23.3%. Economic values came in the fourth place, with 810 values and a percentage of 11.2%. The study recommended the need to focus on the local production of Arabic animation, so that it could include the content that reinforces the children’s positive values.